Cirrhotic Changes in Choledochal Cyst in Relevance to Increasing Age at Presentation - Nabila Talat , Sarfraz Ahmad , Arsalan Raza Wasti , Afzal Mirza , Samina Zaman, Muhammad Saleem , Mahmood Shaukat (Journal of Rawalpindi Medical College, 2016)
Background: To analyze the relationship between the changes to the liver histology with increasing age in patients with choledochal cyst. Methods: In this prospective, descriptive study all the patients presenting with choledochal cyst upto 12 years of age were included. The clinical features, liver function tests, ultrasonography, HIDA scan and per operative cholangiogram were selectively done. A total of 53 patients underwent hepatico-jejunostomy. Per-operative liver biopsies were taken in all cases and correlation with age of patient was calculated. Results: Ultrasound was found to be a reliable investigation in diagnosing choledochal cyst. CT scan was found to be superior as detailed anatomy could be defined. The histological finding that evolved with increasing age was biliary cirrhosis. The incidence of cirrhotic changes was found to be 50% in children of age group 0-2 years and 63% in 2-12 years age group. The correlation was found significant(p-value= 0.015). Conclusion: Age of the patient with choledochal cyst has significant impact on liver histology. Cirrhosis develops more frequently with increasing age. Early diagnosis and prompt treatment is necessary for a good outcome.